Learning by Doing : a Handbook for Professional Learning Communities at Work, Third Edition - DuFour, Richard, ....-; DuFour, Rebecca, ....-; Eaker, Robert, ....-; Many, Thomas W., ....-; Mattos, Mike. Aut. (Bloomington : Solution Tree Press, 2016)
Discover how to close the knowing-doing gap and transform your school or district into a high-performing PLC. The powerful third edition of this comprehensive action guide updates and expands on new and significant PLC topics. Explore fresh strategies, models, and tips for hiring and retaining new staff, creating team-developed common formative assessments, implementing systematic interventions, and more. Benefits Build a shared knowledge of critical vocabulary and the concepts underlying key PLC terms.Equip yourself with the knowledge and tools necessary to model effective reciprocal accountability.Make honest assessments of your school by examining conventional practices from a fresh, critical perspective.Take immediate and specific steps to close the knowing-doing gap.Move beyond planning, and start doing.   Contents Introduction to the Third Edition 1                 A Guide to Action for Professional Learning Communities at Work™ 2                 A Clear and Compelling Purpose 3                 Building the Collaborative Culture of a Professional Learning Community 4                 Creating a Results Orientation in a Professional Learning Community 5                 Creating a Focus on Learning 6                 Creating Team-Developed Common Formative Assessments 7                 Responding When Some Students Don't Learn 8                 Hiring, Orienting, and Retaining New Staff 9                 Resolving Conflict and Celebrating in a Professional Learning Community 10               Implementing the PLC Process Districtwide.
Keywords: Personeelsbeleid; learning by doing